Super‐resolution analyzing spatial organization of lysosomes with an organic fluorescent probe. Issue 3 (22nd March 2022) - Wang, Lei; Chen, Rui; Han, Guanqun; Liu, Xuan; Huang, Taosheng; Diao, Jiajie; Sun, Yujie
Abstract: Lysosomes are multifunctional organelles involved in macromolecule degradation, nutrient sensing, and autophagy. Live imaging has revealed lysosome subpopulations with dynamics and characteristic cellular localization. An as‐yet unanswered question is whether lysosomes are spatially organized to coordinate and integrate their functions. Combined with super‐resolution microscopy, we designed a small organic fluorescent probe—TPAE—that targeted lysosomes with a large Stokes shift. When we analyzed the spatial organization of lysosomes against mitochondria in different cell lines with this probe, we discovered different distance distribution patterns between lysosomes and mitochondria during increased autophagy flux. By using SLC25A46 mutation fibroblasts derived from patients containing highly fused mitochondria with low oxidative phosphorylation, we concluded that unhealthy mitochondria redistributed the subcellular localization of lysosomes, which implies a strong connection between mitochondria and lysosomes. Abstract : We designed and synthesized an organic small fluorescence probe with a large Stokes shift. With this probe specifically targeting lysosomes, we revealed a distinct spatial organization of lysosomes against mitochondria during mitophagy by using super resolution microscopy.